Mental health and performance: narratives of swedish elite tennis players - Sievert, E. (Halmstad University, School of Health and Welfare, 2022)
Elite athletes often risk their health to achieve the highest level of performance, but this might instead result in decreased performance and health over time. Over the last few years, multiple elite athletes have expressed their struggles with mental health (MH), and it seems like the prevalence for mental illness in elite athletes is comparable to the general population. Multiple factors influence the balance between MH and performance, and it is known that elite athletes experience unique stressors in their careers. The purpose of the study is to explore career narratives of Swedish elite tennis players to learn about how, at different periods of their careers, they searched for, maintained, lost, and restored their perceived optimal balance between MH and performance. The methodology used is narrative inquiry with thematic analysis and composite vignettes to analyze and present the data. Three Swedish elite tennis players were interviewed. The findings show five different themes that create a thematic map which demonstrate the stages the athletes faced and experienced as they attempt to balance MH and high-level performance. It is concluded that sport psychology professionals are obligated to understand how athletes can work towards an optimal balance between MH and performance, and this study provides a step towards that goal.